2022
DOI: 10.1002/cjoc.202200209
|View full text |Cite
|
Sign up to set email alerts
|

Chlorinated Conjugated Polymer Based on Chlorine‐ and Cyano‐substituted (E)‐1,2‐Di(thiophen‐2‐yl)ethane for Ambipolar and n‐Type Organic Thin‐film Transistors

Abstract: Comprehensive SummaryChlorinated conjugated polymers are rarely reported in ambipolar and n‐type organic thin‐film transistors (OTFTs), mainly due to the lack of chlorinated strong electron‐deficient building blocks. Herein, we report three new chlorine (Cl)‐ and cyano (CN)‐ substituted (E)‐1,2‐di(thiophen‐2‐yl)ethane building blocks and their copolymers P2Cl1CNTVT‐DPP, P4Cl1CNTVT‐DPP and P2Cl2CNTVT‐DPP. P2Cl1CNTVT‐DPP and P2Cl2CNTVT‐DPP had nearly planar backbone geometries, mixture of edge‐on and face‐on ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Both PFBDB-T and PFBDB-T-2F showed greater redshifted maximum absorption than that of PBDB-T films, which suggests that F substitution on the thiophene unit in the conjugated backbone enhanced the ICT effect of the CPs. As shown in Figure c, PFBDB-T and PFBDB-T-2F exhibited an increased 0–0/0–1 intensity ratio compared to that of PBDB-T, signifying strongly aggregation behavior . In addition, the maximum absorption cutoffs were found to be 684, 700, and 687 nm for PBDB-T, PFBDB-T, and PFBDB-T-2F, respectively.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Both PFBDB-T and PFBDB-T-2F showed greater redshifted maximum absorption than that of PBDB-T films, which suggests that F substitution on the thiophene unit in the conjugated backbone enhanced the ICT effect of the CPs. As shown in Figure c, PFBDB-T and PFBDB-T-2F exhibited an increased 0–0/0–1 intensity ratio compared to that of PBDB-T, signifying strongly aggregation behavior . In addition, the maximum absorption cutoffs were found to be 684, 700, and 687 nm for PBDB-T, PFBDB-T, and PFBDB-T-2F, respectively.…”
Section: Resultsmentioning
confidence: 95%
“…45 The intensity ratio of 0−0 to 0−1 can reveal the degree of intermolecular aggregation of the polymers. The intensities of the 0−0 peaks were higher than those of the 0−1 peaks for PBDB-T, PFBDB-T, and PFBDB-T-2F, indicating 46 In addition, the maximum absorption cutoffs were found to be 684, 700, and 687 nm for PBDB-T, PFBDB-T, and PFBDB-T-2F, respectively. The highest cutoffs indicated that PFBDB-T with two F substitutions exhibited the strongest ICT effect among the three polymers.…”
Section: T H Imentioning
confidence: 87%
“…[ 13‐15 ] Many donor and acceptor building blocks have been developed to construct D‐A type conjugate polymers. [ 16‐20 ] Amongst these building blocks, benzothiadiazole (BTz) is widely used in the construction of high‐performance D‐A type conjugated polymers due to its merits of rigid planar structure, electron deficiency and structural modifiability. [ 21‐22 ] For example, conjugated polymers obtained by copolymerization of benzothiadiazole with indacenodithiophene (IDT), cyclopentadithiophene (CPDT), diketopyrrolopyrrole (DPP) have achieved high‐performance in OPVs and OFETs devices.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…1–10 The skeleton structures of CPs with high carrier mobility in organic field-effect transistors (OFET) reported in the literature are generally composed of derivatized aromatic units featuring structural diversity, good chemical stability, and so on. 2,11–24 Despite these advantages, their inherent aromatic resonance energy can confine π-electrons to individual aromatic rings to a certain extent, and hence potentially suppress carrier transport through the whole conjugated backbone. 25…”
Section: Introductionmentioning
confidence: 99%